Biogas Production and Nitrogen Recovery from Cattle and Chicken Dung Through Anaerobic Digestion - Malgwi, D. J.; Musa, M. A.; Jones, A. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study was conducted to determine the biochemical methane potential (BMP) of cattle and chicken dung through anaerobic digestion. Essentially, manure from animal waste could be a valuable resource in the production of high-grade organic fertilizer. To achieve this, chicken and cattle dung were collected at Ramat polytechnic farms in Maiduguri for the assessment. All samples were prepared and the digestates analysed to determine the nutrient composition using Atomic Absorption Spectrophotometer (AAS), UK, 2005. Thereafter, the nitrogen (N) content was measure using Kjeldal method. This process was observed for seven (7) days. Finally, the water displacement method was adopted to measure the amount of biogas produced. The results show that at a ratio of 2:3 cattle to chicken dung, the highest gas yield was 117 mg/l on the first (1) day and the lowest gas yield was 53 mg/l using the blank sample on the seventh (7) day. Nevertheless, using blank sample and ratios of 1:1, 2:3, and 3:2, the amounts of nitrogen compounds in the substrates prior to and following digestion were 1.17, 1.66, 2.45, and 2.39 mg/l and 2.17, 2.66, 3.25, and 3.19 mg/l, respectively. Consequently, it is evident that the production of biogas and biofertilizer from agricultural waste has the potential to be a promising technology in low-income society.